Flexible highly-sensitive pressure sensor based on rGO/Fe nanowires composites for wearable human health detection - Cao, Liang; Wu, Rui; Xiang, Hong; Wu, Xiaodong; Hu, Xiaoyan; He, Gaohui; Gui, Yingang (Frontiers in Chemistry, 2024)
Flexible pressure sensors applied in wearable detection often face challenges, such as low sensitivity, large device size, poor flexibility, and long response time. This study aims to design and develop highperformance pressure-sensitive materials for wearable human detection applications. Using a sensitive layer composite and microstructural design, rGO/Fe nanowires (NWs) composites were proposed as the pressure-sensitive material. This approach yields a compact sensor with high flexibility, good mechanical properties, and excellent sensing performance. Firstly, rGO/Fe NWs composites were prepared by the Hummers method and an in-situ reduction technique under a magnetic field. Secondly, the structural design, component construction, and sensing mechanism of the sensors were thoroughly investigated. Finally, the performance of the flexible pressure sensor was tested, and its application in the wearable field was explored. The results demonstrate that the sensor exhibits excellent performance with a good response to both large and small pressures within the range of 0 to 30 kPa, providing an effective method for wearable human health detection.